Strategic Management Change Enhances Organizational Sustainability in the Wedding Service Industry: Perubahan Manajemen Strategis Meningkatkan Keberlanjutan Organisasi di Industri Jasa Pernikahan - Mustafadah, Marta Aulia; Abadiyah, Rifdah (Universitas Muhammadiyah Sidoarjo, 2023)
In response to increasing competition and the time-sensitive nature of the wedding service industry, this qualitative study investigates the effectiveness of change management strategies employed by a wedding service business. Through purposive sampling and data collection methods such as interviews and natural observation, the research demonstrates that strategic management changes implemented by Whulyan Attire have positively impacted organizational sustainability. The study underscores the significance of adaptability and innovation in meeting the evolving demands of the market, offering valuable insights for entrepreneurs seeking to navigate competitive landscapes and temporal constraints in the wedding service sector. Highlights: Effective change strategies. Competitive market dynamics. Sustainable business practices. Keywords: Change Management, Organizational Sustainability, Wedding Service Industry, Competition, Adaptability